DENTIN HYPERSENSITIVITY ASSOCIATED WITH NON-CARIOUS CERVICAL LESION: Narrative review of the literature - Fernandes de Sales, Thaynnara Eduarda (2024)
Dentin hypersensitivity (DH) is a painful condition characterized by an exaggerated response of exposed dentin to external stimuli, such as heat, cold, touch, or acidic substances. This condition is often associated with non-carious cervical lesions (NCCLs), which are defects in the tooth structure located at the cementoenamel junction, resulting from factors such as abrasion, erosion, and abfraction. NCCLs cause the loss of enamel in the cervical region, exposing the underlying dentin and increasing susceptibility to hypersensitivity. The clinical management of DH associated with NCCLs is challenging, requiring a multidisciplinary approach that includes both modifications in oral hygiene habits and diet, as well as the application of desensitizing agents, fluoride varnishes, or laser treatments. Prevention also plays a importante role, emphasizing patient education to reduce behaviors that contribute to dental wear. Although there are several therapeutic options available, tailoring treatment based on the individual needs of each patient is essential for achieving effective and lasting results. Continued research in this area is fundamental to developing more effective approaches for the prevention and treatment of DH associated with NCCLs.